Peranan Manajemen Konflik Pada Suatu Organisasi - Hadrdianti .; Basmalah siarkanasa; Sri inyanti rasang; Faujiyah m. lau; Dzulfiana Parwati; Fidia Laode Hamu (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
Conflict is an inseparable phenomenon of organizational life due to differences in background, interests, values, perceptions, and goals between individuals and work groups. If not managed properly, conflict can have negative impacts such as decreased performance, fracturing work relationships, and weakening the quality of decision-making. However, conflict that is managed appropriately can actually be a source of learning, innovation, and increased organizational effectiveness. Therefore, conflict management plays a strategic role in maintaining organizational stability and sustainability. This discussion aims to examine the meaning of conflict in organizations, the definition of conflict management, the causes of conflict, the objectives and functions of conflict management, the role of conflict management in organizations, and the factors and characteristics of conflict management roles. Conflict management is understood as a planned and continuous process to identify, manage, and resolve conflict constructively to maintain it at a functional level. The results of this discussion indicate that effective conflict management can enhance communication, improve work relationships, enrich the decision-making process, and encourage the creation of a healthy, adaptive, and productive organizational culture.